2014
DOI: 10.1007/s00125-014-3379-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of mouse embryonic pancreas to metformin enhances the number of pancreatic progenitors

Abstract: Aims Developing beta cells are vulnerable to nutrient environmental signals. Early developmental processes that alter the number of pancreatic progenitors can determine the number of beta cells present at birth. Metformin, the most widely used oral agent for diabetes, alters intracellular energy status in part by increasing AMP-activated protein kinase (AMPK) signaling. This study examined the effect of metformin on the developing pancreas and beta cells. Methods Pancreatic rudiments at embryonic day 13.0 (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…Recent finding suggested that metformin could also interact with mammalian target of rapamycin complex 1 (mTORC1) signaling as well as pancreatic and duodenal homeobox 1 (PDX1) thus affecting pancreatic functions [21]. Besides, metformin has been shown to affect Farnesoid X Receptor (FXR) activities through AMPK-FXR crosstalk [22].…”
Section: Discussionmentioning
confidence: 99%
“…Recent finding suggested that metformin could also interact with mammalian target of rapamycin complex 1 (mTORC1) signaling as well as pancreatic and duodenal homeobox 1 (PDX1) thus affecting pancreatic functions [21]. Besides, metformin has been shown to affect Farnesoid X Receptor (FXR) activities through AMPK-FXR crosstalk [22].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicates that metformin directly acts on pancreatic β-cells [1]; nevertheless, the effect of metformin on β-cells remains controversial. Studies have shown that metformin inhibits β-cell apoptosis induced by hyperglycemia or hyperlipidemia [2,3] and enhances the number of pancreatic progenitor cells in the mouse embryonic pancreas [4], while other studies have indicated that metformin has a dual role in MIN6 pancreatic β-cell function through the AMPK-dependent autophagy pathway [5]. Therefore, the exact regulation mechanisms of metformin on β-cells need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The results imply that prenatal exposure of metformin can affect long-term metabolic reprogramming in offspring. These concerns were also echoed in in vitro studies by Gregg et al [ 29 ] and Vazquez-Martin et al [ 59 ]. When metformin is introduced to mESCs and developing mouse pancreata, both showed significant changes in expression levels of markers reflective of their functions and specific characteristics: pluripotency factors in mESCs [ 59 ] and pancreatic progenitor markers in prenatal pancreatic islets [ 29 ].…”
Section: Current Studies and Models Of Prenatal Metformin Exposurementioning
confidence: 90%
“…1 ). Gregg et al showed that in utero exposure to metformin leads to more cells expressing Pdx1 (a pancreatic progenitor marker), but less cells expressing Ngn3 (a later pancreatic endocrine progenitor marker) in mouse embryos [ 29 ]. As the endocrine progenitors are the precursors of mature pancreatic beta cells, the decrease in endocrine progenitor population will likely cause a decrease in the eventual proportion of mature beta cells.…”
Section: The Varied Actions Of Metformin In Different Human Tissues Cmentioning
confidence: 99%